2012
DOI: 10.3347/kjp.2012.50.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Abundance of Biting Midges, Culicoides spp. (Diptera: Ceratopogonidae), Collected at Cowsheds in the Southern Part of the Republic of Korea

Abstract: Black light traps were used to measure the seasonal and geographical distribution of Culicoides spp. (biting midges or no-see-ums) at 9 cowsheds in the southern half of the Republic of Korea (ROK) from June through October 2010. A total of 25,242 Culicoides females (24,852; 98.5%) and males (390; 1.5%) comprising of 9 species were collected. The most commonly collected species was Culicoides punctatus (73.0%) followed by C. arakawae (25.7%), while the remaining 7 species accounted for <1.0% of all Culicoides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…The species of the biting midge of the genus Culicoides (Diptera: Ceratopogonidae) most commonly collected on cattle farms was Culicoides (C.) punctatus , followed by C. arakawae [ 13 ]. This result is consistent with those of previous seasonal abundance observations of cowsheds conducted in the southern part of the Republic of Korea [ 7 ]. However, the isolation of bovine arboviruses from Culicoides biting midges and the identification of the main vector species remain subjects for a future study.…”
supporting
confidence: 93%
“…The species of the biting midge of the genus Culicoides (Diptera: Ceratopogonidae) most commonly collected on cattle farms was Culicoides (C.) punctatus , followed by C. arakawae [ 13 ]. This result is consistent with those of previous seasonal abundance observations of cowsheds conducted in the southern part of the Republic of Korea [ 7 ]. However, the isolation of bovine arboviruses from Culicoides biting midges and the identification of the main vector species remain subjects for a future study.…”
supporting
confidence: 93%
“…Whereas males are not blood feeders and usually die after mating. Similar, sex wise prevalence pattern were also reported by Satheesha et al (2006), Reddy and Hafeez (2008), Deniz et al (2010), Foxi and Delrio (2010) and Kim et al (2012). During this study, 10 different Culicoides spp.…”
Section: Resultssupporting
confidence: 71%
“…Musuka et al (2001) reported from Zimbabwe, Kline (1986) from Salt Marsh in Florida, USA, Deniz et al (2010) from Thrace Region of Turkey, Kim et al (2012) from Southern part of the Republic of Korea, Aybar et al (2012) from Salta, Northwestern Argentina, Oem et al (2013) in Korea. The species composition in different countries varied which could be probably due to the prevailing different agroclimatic and seasonal conditions.…”
Section: Resultsmentioning
confidence: 99%
“…collected from cattle and poultry farms in Gyeonggi-do reported much later [ 5 ]. More recently, a brief history of the Culicoides fauna of Korea was reported by Kim et al [ 6 ] along with new records of 3 Culicoides spp. ( C. nasuensis Kitaoka, C. pallidulus Yu, and C. jacobsoni Macfie) [ 7 ], bringing the total number of confirmed records of Culicoides spp.…”
mentioning
confidence: 99%
“…Traps were operated continuously, and specimens were collected twice per month from May-November 2013. Midges were processed as described previously [ 6 ] and identified using the morphological keys and descriptions of Arnaud [ 10 ] and Wada [ 11 ] and the checklist for Korea [ 7 ].…”
mentioning
confidence: 99%